2021
DOI: 10.1021/acs.inorgchem.0c03216
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II) Metal–Organic Framework with unh Topology and Tetrazole-Padded Helical Channels

Abstract: A unique metal–organic framework (MOF) with tetrazole-padded helical channels has been successfully synthesized in one pot from iron­(II) trifluoromethanesulfonate, 4-formylimidazole, hydrazine, and sodium azide under solvothermal conditions and features a rare unh topology and porous structure for gas adsorption. Transformations of condensation, cycloaddition, and coordination occurred during the synthetic process, in which a 1,5-disubstituted tetrazole ligand was formed in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Low-valent metals (soft acid) coordinating with N-containing linkers (soft base) form robust MOFs based on the hard and soft acid–base principle, and Cu­(I)-based complexes possess excellent fluorescence as a result of the d 10 close shell of the Cu­(I) ion, , which benefits the implementation of fluorescence sensing. In addition, tetrazoles and their derivatives are an important class of N-donor ligands and have been well established for achieving porous MOFs, , in which tetrazolate nitrogen atoms, if not bound to metals, can participate in prolific hydrogen bonding with guest water molecules in the pores, which is ideal for constructing superior proton conductors.…”
Section: Introductionmentioning
confidence: 99%
“…Low-valent metals (soft acid) coordinating with N-containing linkers (soft base) form robust MOFs based on the hard and soft acid–base principle, and Cu­(I)-based complexes possess excellent fluorescence as a result of the d 10 close shell of the Cu­(I) ion, , which benefits the implementation of fluorescence sensing. In addition, tetrazoles and their derivatives are an important class of N-donor ligands and have been well established for achieving porous MOFs, , in which tetrazolate nitrogen atoms, if not bound to metals, can participate in prolific hydrogen bonding with guest water molecules in the pores, which is ideal for constructing superior proton conductors.…”
Section: Introductionmentioning
confidence: 99%
“…84 Tetrazoles can also be used to construct MOFs. 85,86 In 2016, Biswas and co-workers reported the formation of a 3D-amide functionalised Cd(II) MOF with a tetrazole-based organic ligand. This MOF [Cd 5 Cl 6 (12) The steady-state fluorescence titration experiment of activated 13 showed that it could selectively detect 2,4,6-trinitrophenol (TNP) with a detection limit of 1.87 Â 10 À7 M (42.84 ppb).…”
Section: Tetrazole-based Polymeric Assembliesmentioning
confidence: 99%
“…Tetrazoles can also be used to construct MOFs. 85,86 In 2016, Biswas and co-workers reported the formation of a 3D-amide functionalised Cd( ii ) MOF with a tetrazole-based organic ligand. This MOF [Cd 5 Cl 6 ( 12 )(H- 12 ) 2 ]·7H 2 O ( 13 ), (H 2 - 12 = 4-(1 H -Tetrazol-5-yl)-N-[4-(1 H -tetrazol-5-yl)phenyl]benzamide) ( 12 ), was synthesised by the reaction of CdCl 2 ·H 2 O ( 11 ) and 12 in 2 : 1 molar ratio in a DMF–MeOH (1 : 1) solution at 80 °C (Fig.…”
Section: Tetrazole-based Polymeric Assembliesmentioning
confidence: 99%
“…Tetrazole ligands are important aromatic heterocyclic compounds mainly because of their attractive structural features and comprehensive applications in coordination chemistry, synthetic chemistry as well as medicinal chemistry. On the other hand, TPE is an archetypal luminogen that shows AIE property. Fusing these two moieties into one system may lead to the generation of new functional ligand materials with combined advantages of both components, which not only have rich coordination behavior affording different types of MOFs with novel topologies but also possess interesting photoelectric properties.…”
Section: Introductionmentioning
confidence: 99%